Impact of ACEI/ARB use on COVID-19 mortality in patients with ischaemic heart disease: insights from South Korean National health insurance service data - Kim, Shin-Woo; Goo, Taewan; Noh, Seunghwan; Lee, Seungyeoun; Oh, Bumjo; Park, Taesung (BMC infectious diseases, 2025)
Background The COVID-19 pandemic has highlighted the importance of understanding the complex interactions between pre-existing conditions, such as ischaemic heart disease (IHD), and mortality risk. This study aims to investigate the associations among COVID-19 mortality, the presence of IHD, and the use of angiotensin receptor blockers (ARBs) and angiotensin-converting-enzyme inhibitors (ACEIs) by leveraging the South Korean National Health Insurance Service (NHIS) big data. Methods We conducted a retrospective cohort study of 30,056 patients with COVID-19 from the NHIS. The study population was stratified into four groups based on IHD status and the use of ACEI/ARBs. To assess their effects on mortality, we applied inverse probability of treatment weighting (IPTW) to balance baseline covariates, followed by a weighted logistic regression. The interaction between IHD and ACEI/ARB use was evaluated on both multiplicative (interaction term) and additive scales (Relative Excess Risk Due to Interaction, RERI), supplemented by an age-stratified analysis (≤ 70 vs. >70 years). Results Among 30,056 COVID-19 patients, we identified a significant interaction between IHD and ACEI/ARB use on mortality after adjusting for confounders. The main finding revealed that among patients with IHD, ACEI/ARB treatment was associated with 74% lower odds of mortality compared to non-treatment (Adjusted OR: 0.26, 95% CI: 0.08–0.92, p = 0.037). This protective interaction was strongly age-dependent, remaining statistically significant only in patients older than 70 (Interaction OR: 0.53, 95% CI: 0.27–0.99; p = 0.048). Furthermore, a significant antagonistic interaction on the additive scale (RERI: − 1.77, 95% CI − 3.04 to − 0.51; p = 0.006) confirmed a combined protective effect greater than the sum of the individual effects. Conclusions This study leverages the NHIS big data to provide a comprehensive analysis of the complex interactions among IHD, ACEI/ARB use, demographic factors, and comorbidities in the context of COVID-19 mortality. Our findings suggest a 45% reduction in the odds of mortality for IHD patients taking ACEI/ARB, particularly those over 70 years, but randomised controlled trials are needed before clinical guideline changes. The findings highlight the protective effect of ACEI/ARB in patients with IHD and emphasize the importance of personalized treatment approaches considering patient characteristics, pre-existing conditions, and medication use.